Teaching Receptive Skills To ESL And EFL Learners (Journal of Pedagogical Inventions and Practices, 2024)
This article delves into the effective teaching of receptive skills—reading and listening—to ESL and EFL learners. Recognizing the pivotal role these skills play in language acquisition and real-world communication, the article offers comprehensive insights into understanding, addressing challenges, and implementing successful instructional strategies. It explores various approaches, including pre-teaching vocabulary, utilizing authentic materials, and incorporating diverse activities to engage learners. Emphasis is placed on assessment methods and cultural considerations. Through this exploration, educators gain practical tools to enhance their teaching practice and empower learners to develop proficiency in receptive skills, ultimately fostering effective language communication.